Multi-Step Regulation of the TLR4 Pathway by the miR-125a~99b~let-7e Cluster - Curtale, Graziella; Renzi, Tiziana A.; Mirolo, Massimiliano; Drufuca, Lorenzo; Albanese, Manuel; De Luca, Mariacristina; Rossato, Marzia; Bazzoni, Flavia; Locati, Massimo (Frontiers in Immunology, 2018)
An appropriate immune response requires a tight balance between pro- and anti-inflammatory mechanisms. IL-10 is induced at late time-points during acute inflammatory conditions triggered by TLR-dependent recognition of infectious agents and is involved in setting this balance, operating as a negative regulator of the TLR-dependent signaling pathway. We identified miR-125a~99b~let-7e as an evolutionary conserved microRNA cluster late-induced in human monocytes exposed to the TLR4 agonist LPS as an effect of this IL-10-dependent regulatory loop. We demonstrated that microRNAs generated by this cluster perform a pervasive regulation of the TLR signaling pathway by direct targeting receptors (TLR4, CD14), signaling molecules (IRAK1), and effector cytokines (TNFα, IL-6, CCL3, CCL7, CXCL8). Modulation of miR-125a~99b~let-7e cluster influenced the production of proinflammatory cytokines in response to LPS and the IL-10-mediated tolerance to LPS, thus identifying this gene as a previously unrecognized major regulatory element of the inflammatory response and endotoxin tolerance.